Immigrant Subjecthood in Souvankham Thammavongsa’s "How to Pronounce Knife" (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
The introductory part of the paper discusses the concept of subjecthood and relates it to the contemporary Canadian immigration policy and the deep-rooted ethnocentric and racial discriminatory practices against non-citizens – migrants, immigrants, refugees and illegal immigrants. The specific focus of the paper is the female immigrant subjecthood as represented in the collection of stories How to Pronounce Knife (2020) by Souvankham Thammavongsa – born in a Lao refugee camp in Thailand, but brought up in Canada. As the collection progresses, the seemingly disconnected and (extra)ordinary narratives of individual characters start to appear as a single narrative of generations of Lao refugees. Moreover, the fact that Thammavongsa herself came to Canada in the period when it received the greatest number of Southeast Asian refugees suggests that perhaps the material for these stories does not belong solely to fiction, but the accounts of her countrymen and women. Moreover, the manner in which the author manages to bring together these individual accounts into a narrative of the entire group by weaving threads of the shared experiences of discrimination – racial, ethnic and gendered, alienation, isolation, hope and hopelessness, cultural differences and the conflict between the new identity and the old, among other things, represents invaluable contribution to immigrant literature. Therefore, the second part of the paper discusses the intersectional nature of discrimination of female immigrants. The concluding remarks reflect on the impact of the implicit discriminatory practices against immigrants, and particularly women
Keywords: immigrant literature; female subjecthood; contemporary Canadian literature; gender discrimination